Psoriasis and Metabolic Syndrome - Sales, R. (2015)
Psoriasis is a chronic, systemic inflammatory disease associated with several cardiometabolic comorbidities, such as obesity, insulin resistance, dyslipidemia, and hypertension, and with clinically significant increased risk of cardiovascular disease and cardiovascular mortality. These comorbidities are components of the metabolic syndrome. Multiple epidemiologic studies have revealed a high prevalence of metabolic syndrome in patients with psoriasis compared with other skin diseases. Genetic susceptibility and overlapping inflammatory pathways may be potential biologic links underlying this association. Understanding the interrelationship between these conditions is important for the management of psoriasis and its associated comorbidities. This review will focus on the range of these comorbidities, with emphasis on the metabolic syndrome, aiming to encourage physicians to screen patients with psoriasis for cardiometabolic disorders and risk factors